Acute response to cardiac re-synchronization therapy: ventricular properties adaptation?. (25th November 2020) - Degiovanni, A; Gravellone, M; Erbetta, R; Dell' Era, G; Marino, P.N; Patti, G
Abstract: Background: Cardiac re-synchronization therapy (CRT) reduces mortality and hospitalization in patients with heart failure, reduced left ventricular ejection fraction (LVEF) and left bundle branch block (LBBB). However, there is no conclusive evidence on baseline parameters able to discriminate responder vs non-responder patients. Purpose: In this study, we tested whether echocardiographic parameters describing LV dyssynchrony and efficiency may predict an acute LV recovery after CRT and whether lead position can modify such relationship. Methods: We enrolled 65 consecutive patients (75% males, aged 71.2±10.5 years) referred for CRT according to current guidelines; 45% had an underlying ischaemic cardiopathy and 1/3 of them presented diabetes mellitus. We performed a CRT-off and CRT–on 2D and 3D echocardiography during devices optimization (time between programming change 10/12 min). We evaluated ventricular dyssynchrony by speckle-tracking analysis based on temporary uniformity of strain (TUS) 3D longitudinal and circumferential. We also derived non-invasive myocardial efficiency (Effic) by interaction between pressure work index (PWI), representing an estimation of myocardial oxygen consumption, and mechanical external work. We indicated as concordant those patients presenting a LV lead position (defined from a chest X-ray using 2 orthogonal views) in the same segment as the latest systolic 3D circumferential strain curves. Results: In the CRT-on phase, a non-statistically significant raise in LVEF was observed [from 0.37 (0.28–0.46) to 0.41 (0.34–0.47), p=0.27]. No improvement in both longitudinal and circumferential 3D TUS was demonstrated during CRT-on (p=0.44 and 0.47, respectively). Conversely, the gain in Effic from CRT-off to CRT-on phase was overall significant (from 0.43±0.14 to 0.50±0.16; p<0.001). After switching to CRT-on, the increase in longitudinal 3D TUS was higher in concordant compared to discordant patients (from 0.83±0.08 to 0.87±0.07 vs 0.88±0.11 to 0.87±0.12, respectively), but without significant interaction (interaction p 0.24). No interaction was also found between variations of PWI after switching to CRT-on and LV lead position (concordant: from 12.99±4.18 to 12.84±2.99 ml/min/100g; discordant: from 13.58±3.89 to 13.95±3.97 ml/min/100g; interaction p 0.75). Conclusions: Effic was overall acutely augmented during CRT-on phase in patients with LV dysfunction undergoing cardiac re-synchronization. In the acute phase, no significant relationship between LV changes in speckle-tracking analyses after CRT and LV lead position was found. Funding Acknowledgement: Type of funding source: None